Synthesis and Characterization of Griseofulvin Derivatives as Microtubule‐Stabilizing Agents. Issue 43 (16th November 2022) - Firdous, Farhat; Ibrahim, Rida; Furqan, Muhammad; Khan, Hina; Raza, Hadeeqa; Singh, Upendra; Emwas, Abdul‐Hamid; Jaremko, Mariusz; Chotana, Ghayoor Abbas; Faisal, Amir; Saleem, Rahman Shah Zaib
Abstract: Microtubules have been an attractive target of cancer drug discovery due to their highly dynamic nature during mitosis. Griseofulvin, a natural antifungal compound, is known to interfere with microtubule dynamics. In the present study, we prepared and analyzed twenty‐seven novel griseofulvin derivatives. Three of these compounds had GI50 values <10 μM (5.74 to 9.7 μM) in breast cancer cell line CAL‐51. The most promising compound ((2S, 6'R)‐4'‐(benzhydrylamino)‐7‐chloro‐4, 6‐dimethoxy‐6'‐methyl‐3H‐spiro[benzofuran‐2, 1'‐cyclohexan]‐3'‐ene‐2', 3‐dione), was characterized as a microtubule‐stabilizing agent with a GI50 value of 5.74±1.43 μM compared to 10.79±3.06 μM GI50 for parental griseofulvin. It also inhibited the proliferation of other cancer cell lines, including KB‐3‐1 and HCT116, with GI50 values of 1.19±0.34 μM and 2.48±0.40 μM, respectively. Treatment of cancer cells with it resulted in aberrant mitosis causing G2/M arrest. Finally, we show that this compound increased the expression of p53 protein and induced apoptotic cell death. Abstract : In the present study, we show synthesis and analysis of twenty‐seven griseofulvin derivatives (2, 4 a —4 z ). We demonstrate that the most promising compound causes aberrant mitosis (G2/M arrest), stabilizes microtubules, increases the expression of p53 and induces apoptotic cell death.